Holistic Marketing Approach in the Global Fashion Industry: The Features of Post-COVID Development - Duginets Ganna V.; Novak Olena V. (Bìznes Inform, 2023)
In the era of digital transformations, successful business activities require a rethinking of traditional marketing concepts in order to introduce more integrated approaches to promote their own goods and services. In the XXI century, a paradigm shift towards holistic marketing, which, among other things, recognizes the new scale and complexity of marketing and seeks to harmonize old approaches with innovative ones, is being established. The COVID-19 crisis that developed in 2020-2021 negatively affected the fashion industry, primarily because of a decrease in demand and, accordingly, in production volumes. Taking into consideration the matter that in Ukraine in the last decade the fashion and textile industries have become a socioeconomic stimulus for the economic development of the country, it is relevant to identify the features of the post-COVID development of the world fashion industry in order to further substantiate what can be used to restore the Ukrainian fashion industry in the post-war period. The aim of the study is to identify the spread of the concept of holistic marketing as one of the features of the development of the worldwide fashion industry in the post-COVID period. The study was carried out using the methods of theoretical generalization, comparative analysis, synthesis, induction and deduction, which made it possible to define the risk factors of the COVID-19 pandemic for business, as well as to substantiate the peculiarities of spreading the concept of holistic marketing in the global fashion industry in the post-COVID period. As result of the analysis of factual material, approaches to understanding holistic marketing in the worldwide fashion industry through identification of its components (internal and integrated marketing, relationship marketing, as well as socio-ethical marketing) have been generalized. It is proved that the practices of using holistic marketing, namely, its socio-ethical component, can be considered as a means of introducing a sustainable model of design and production of fashionable products in the post-COVID period. Thus, in the post-COVID period, the global fashion industry should try to better support educational programs for workers, socially responsible sewing workshops, give priority to local traditions and social entrepreneurship in each region where elements of the production chain are located. It is substantiated that in order to develop the Ukrainian fashion industry, it is necessary to introduce a systemic, organizational, and managerial models of holistic marketing that meets the challenges of the XXI century. Future research in this scientific area is planned to focus on the development of a holistic marketing approach system, based on the differentiated needs of domestic subjects of the fashion industry in the post-war period, taking into account significant differences compared to the post-COVID period of activity.